FAMILY CARE: A CRITICAL REVIEW - de la Cuesta Benjumea, Carmen (Investigación y Educación en Enfermería, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Family care is an increasingly common phenomenon that is situated in the private domain and characterized as a feminine domain. Because of this, it is a pending issue in the public policy of some countries. Objetive: the paper explores the family care literature to highlight significant gaps in three issues: the nature of care, the burden of care and t responses to alleviate this burden. The aim is to make visible an area of interest in Public Health and Nursing. Results: it is argued that family care has intangible features and therefore it is amenable to research using qualitative methods. It is also argued that the burden of care must be considered as an issue of inequity in health. Conclusions: the area of family care requires today more research and diverse approaches as without a wide understanding of family care there cannot be effective intervention; in addition, collective health, understood as a study area, would benefit from the subjective and social constructions of qualitative research studies.